Exploring the magic bullets to identify Achilles' heel in SARS-CoV-2: Delving deeper into the sea of possible therapeutic options in Covid-19 disease: An update. (January 2021) - Thakur, Shikha; Mayank,; Sarkar, Bibekananda; Ansari, Arshad J.; Khandelwal, Akanksha; Arya, Anil; Poduri, Ramarao; Joshi, Gaurav
Abstract: The symptoms associated with Covid-19 caused by SARS-CoV-2 in severe conditions can cause multiple organ failure and fatality via a plethora of mechanisms, and it is essential to discover the efficacious and safe drug. For this, a successful strategy is to inhibit in different stages of the SARS-CoV-2 life cycle and host cell reactions. The current review briefly put forth the summary of the SARS-CoV-2 pandemic and highlight the critical areas of understanding in genomics, proteomics, medicinal chemistry, and natural products derived drug discovery. The review further extends to briefly put forth the updates in the drug testing system, biologics, biophysics, and their advances concerning SARS-CoV-2. The salient features include information on SARS-CoV-2 morphology, genomic characterization, and pathophysiology along with important protein targets and how they influence the drug design and development against SARS-CoV-2 and a concerted and integrated approach to target these stages. The review also gives the status of drug design and discovery to identify the drugs acting on critical targets in SARS-CoV-2 and host reactions to treat Covid-19. Graphical abstract: Image 1 Highlights: SARS-CoV-2 is the seventh coronavirus strain reported to infect Homo sapiens . Remedesvir has been approved for the treatment of Covid-19. The druggable targets of the virus include spike protein, membrane protein, protease, envelope protein, hemagglutinin esterase, nucleocapsid protein, and helicase proteins. Host and virus interactions result in inflammation, and multiple organs damage are plausible switches for drugs to act to combat Covid-19. Apart from synthetic drugs, active ingredients derived from natural/herbal and fruits are also being exploited for their effectiveness against SARS-CoV-2.